Cryptographic libraries for developers - Ed Moyle (Charles River Media, 2006)
Learn to Use the Right Cryptography Library Everytime! No longer is it an option for software to include cryptography; everyone from office suites to accounting software and eCommerce Web sites use it. So today's developers have to know how to write software that includes cryptographic functionality. Although they are usually familiar with the basics of cryptography, they are not always familiar enough with the available products to select the right API/library and get up and running with it quickly. Cryptographic Libraries for Developers teaches developers about the available APIs and helps them select the right ones for their projects based on platform, language, and regulatory requirements. The book serves as a nuts and bolts guide to writing software using these libraries and provides abundant examples and detailed examples throughout. The libraries covered include OpenSSL, B/Safe, the Java Cryptographic Library (JCE,) as sign/verify, encrypt/decrypt (asymmetric and symmetric,) MACs, and Hashing, as well as higher-level primitives such as X.509 digital certificates and secure (SSL) communications